Behavioral and Morphological Studies of the Membranous Tergal Structure of Male Blattella germanica (Blattodea: Ectobiidae) During Courtship. Issue 5 (22nd October 2019) - Shimomura, Kenji; Ishii, Daisuke; Nojima, Satoshi
Abstract: The male German cockroach Blattella germanica (L.) exhibits a characteristic courtship display by raising its wings, turning around, and exposing its tergal glands on the seventh and eighth tergites to the female. The male secretes a courtship pheromone from the tergal glands which induces a strong feeding response in the female, facilitating copulation. Upon multiple, detailed microscopic observations of the courtship display, we found that the male markedly expanded the intersegmental area between the sixth and seventh tergites, but deflated this area as soon as it perceived a tactile stimulus on its back by the female, while continuing to raise its wings and exposing the tergal glands. The intersegmental area is composed of two parts: a membranous posterior part of the sixth tergite, and the regular intertergal membrane. The membranous posterior part was found to be crescentic in shape and clearly separated from the intertergal membrane by traverse tongue-shaped plates. Scanning electron microscopic observation revealed that there were many orifices or pores in the membranous crescentic zone, and its morphological structure was clearly different from that of the intertergal membrane. Our observations suggest that the crescentic zone is likely a secretory gland that may play an important role at the beginning of the male courtship display, different from the tergal glands.